PEMODELAN FISIK BENDUNGAN UNTUK PENGAMATAN GARIS FREATIS BERDASARKAN KEMIRINGAN LERENG SEBELAH HULU - Azmeri Azmeri; Maimun Rizalihadi; Rima Vinanda (JURNAL TEKNIK SIPIL, 2013)
Seepage problems that often appeared on a main-dam. The purpose of this study is to observe the flow pattern of phreatic line that occur on the dam body and to count the seepage discharge that come about. This research was conducted using the seepage body model that made from yellowish clay with 70 % levels of density and had 4,9 x 10-7 permeability values which variating upstream slope angle. The amount of upstream slope angle that variated was 41,15°, 46,29°, and 52,74°, whereas the downstream was 50,33°. This model test research utilized 10 mm thick glass vassel with 180 cm length, 44 cm width, and 68 cm high as well as 1 : 25 scale from the old researcher. This research had 3 high water catchment variations, those were 35 cm, 45 cm, and 55 cm. In this research, in the 41,15°, 46,29°, and 52,74° upstream slope angle, only in the 55 cm water catchment condition that meet Cassagrande Method. The amount of discharge produced from the calculation and physical modelling each for are for 41,15°, 46,29°, 52,74° was 6,01 x 10-6 cm3/det and 7,96 x 10-6 cm3/det, 5,37 x 10-6 cm3/det and 7,21 x 10-6 cm3/det, 5,81 x 10-6 cm3/det and 7,65 x 10-6 cm3/det. The discharge differenciation from the calculation result and the research showed that calibration modeling is not yet perfect. The result, obtaining from this study represented that the dam body condition accompanied by variating the upstream slope angle also affects the size of the seepage that occurs.